A experimentação no ensino de Biologia: contribuições da teoria do ensino desenvolvimental para a formação no pensamento teórico - Miranda, Edna Sousa de Almeida (2017)
The research aim scientific experimentation in the teaching of Biology and the contributions of the theory of developmental teaching for the development of theoretical thinking in this discipline. We start from the assumption that school education plays a fundamental role in human psychic development, since it allows the access and internalization of the knowledge historically accumulated by humanity under the forms of science, art and philosophy. We focus on the historical-cultural theory and the theory of developmental teaching (VIGOTSKI, 2001, DAVIDOV, 1985, 1988, 1999) to problematize the relationship between scientific experimentation in the laboratory and the learning of biology concepts, highlighting the possible contributions of the theory of developmental teaching to the formation of students' theoretical thinking. The general objective of our research is to identify and analyze how scientific experimentation in Biology teaching can contribute to the development of theoretical thinking, seeking to understand the epistemological, psychological and pedagogical fundamentals of developmental teaching theory by articulating them to the teaching of biology. For this, we use methodological procedures as a bibliographic research on the production of confectionery in respect to scientific experimentation in Biology teaching in dissertations and theses in the west-central region and scientific events of the area (EREBIO / ENEBIO / ENPEC) no period of 2011 to 2016 and the accomplishment of a didactic-formative experiment with students of the first year of the High School of the IFMT, campus Bela Vista, in the city of Cuiabá-MT. The bibliographic review showed that positivist and empirical concept gives science and the conception traditional of teaching, of its genesis in the initial teacher training, hide the understand from the scientific experimentation paper in the teaching two contents of Biology, constituting itself as part of general mode organization from the teaching this discipline. The didactic-formative experiment accomplished of with the students of the first year revealed still of embryonic way or process of breaking as empirical thought or development of a more elaborate and conscious way of thinking. The organization of the Biology teaching with scientific experimentation from the developmental perspective can effectively lead to the apprenticeship and development of two biological concepts. In spite of some limitations, to accomplish the didactic-formative experiment, we can see important contributions of the methodological proposal of Davidov as the understanding of the science as a human construct for the formation of conceptual thought and mediating role of teacher between student and knowledge in this investigative process of biological concept, in this case, a cellular division, and for or understanding of Biology in your totality. We certify that a scholar teaching who has been organized at developmental perspective will be able to fulfill his or her role at the development from a period of time to acess or systematized cooperation in the realm of life transformation.